ANALISIS PEMILIHAN LEMBAGA RISET GUNA MENDUKUNG PENELITIAN DAN PENGEMBANGAN INDUSTRI PERTAHANAN BAWAH AIR - D Aris Susanto; Rudi Lazuardi; Hervianto Nugroho (AGUSPATI Research Institute, 2022)
The threat of underwater warfare in the future is increasing with technological developments. The Indonesian Navy has the task of building and fostering maritime defense forces, one of which is the capability of underwater warfare. Underwater warfare capabilities are fostered by carrying out research and development in order to increase the independence of the national underwater maritime defense industry. In carrying out research and development, it is necessary to analyze the partners of higher education institutions based on the specified criteria. The results of the AHP analysis show that ITB has the highest value compared to ITS and UNHAS.